The Origin of Oil Plunge in Political Economy and Aftermath on the Oil Price - Yusof, Muhammad Suhaimi Mohd; Romle, Abd Rahim; Udin, Mashitah Mohd; Kamal, Mohd Khirul Azwan Mohd; Azmi, Muhammad Aqmarul Azri (International Journal of Economics and Financial Issues, 2016)
Since the past decades, humans watched the changes of politic and economy in the world from the small campaign into huge riot. This kind of events happened all over the world due to the demand for the better administration and ruler had increased until today. Nowadays, the world witnessed the effects of the political economic on the human needs. However, oil price is the major parts of the human needs which affected due to the world political economy revolution. As the revolution increase from time to time, the oil price faced challenges and dilemma in terms of the rise and fall of the oil prices. Oil industry plays huge roles on the social development and economy as it effects all the countries in the world as well. Nevertheless, the oil price cannot be analysed theoretically and practically based on the political issues in the oil producer country while political economy hold the vital role in determining the right price of the oil in the world. Keywords: price, economics, politics, fuel, gas, war and oil JEL Classifications: Q21, P48